1983
DOI: 10.1016/s0735-1097(83)80340-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic actions of high plasma concentrations of propranolol in human subjects

Abstract: The authors have previously shown that 40% of patients whose ventricular arrhythmias respond to propranolol require plasma concentrations in excess of those producing substantial beta-receptor blockade (greater than 150 ng/ml). However, the electrophysiologic actions of propranolol have only been examined in human beings after small intravenous doses achieving concentrations of less than 100 ng/ml. In this study, the electrophysiologic effects of a wider concentration range of propranolol was examined in nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…For example, in the report by Priori et al the specific β-blocker was known in 69% of cases and this was either propranolol or nadolol 40. As we have demonstrated in this study, propranolol may offer specific advantages in treating certain SCN5A mutations because of apparent local anesthetic-like properties of the drug 18,19. By contrast, we recently determined that nadolol has no activity against sodium channels (Wang, D.W., unpublished observations).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…For example, in the report by Priori et al the specific β-blocker was known in 69% of cases and this was either propranolol or nadolol 40. As we have demonstrated in this study, propranolol may offer specific advantages in treating certain SCN5A mutations because of apparent local anesthetic-like properties of the drug 18,19. By contrast, we recently determined that nadolol has no activity against sodium channels (Wang, D.W., unpublished observations).…”
Section: Discussionmentioning
confidence: 57%
“…Propranolol is a widely used β-adrenergic receptor antagonist, but early studies indicated that this drug also exhibits anti-arrhythmic (“membrane stabilizing”) properties at high serum concentrations possibly from effects on voltage-gated sodium channels 18,19 Figure 7A. illustrates that both WT and G1631D channels are blocked by 3µM propranolol during repetitive stimulation (1Hz).…”
Section: Resultsmentioning
confidence: 99%
“…High concentrations of propranolol were required to significantly inhibit cell proliferation, with IC 50 values ranging from 100 μM to >250 μM across the panel of cell lines. Early pharmacokinetics studies revealed that clinically relevant concentrations of propranolol are in the low μM range [35, 36], thus suggesting that propranolol alone is not likely to inhibit cell proliferation in vivo . The sensitivity to propranolol was cell type specific but did not depend on the tissue of origin, since all 4 cell lines of breast tissue origin displayed different levels of sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Vaughan Williams [236] described APD prolongation in the rabbit myocardium, but subsequent studies both confirmed and failed to reproduce this effect [54]. Except for sotalol, there is no conclusive effect on ventricular repolarization of beta-blocking agents that may result in antiarrhythmic or proarrhythmic effects.…”
Section: Characteristics Of Proarrhythmia After Drug-lnduced Qt Prolomentioning
confidence: 99%